The Influence of Personal and Psychological Factors toward Consumer Purchase Decision (Case Study: PETERSAYSDENIM, Bandung) - Vici Fitrayanti; Purwanto Purwanto (Management and Leadership Study Programme, 2020)
The purpose of this research is to analyze the influence of personal and psychological factors toward consumer purchase decision of PeterSaysDenim in Bandung. Those factors are important to the company because it would influence in consumer purchase decision on company’s product. This research uses quantitative analysis with has six independent variables (motivation, belief and attitudes, occupation, economic situation, personality and self-concept, and lifestyle) and one dependent variable (purchase decision). The analysis method that is used in this research is multiple linear regressions. The result shows that, there are partial significant influence of motivation, personality and self-concept, and lifestyle, and no partial significant influence toward consumer purchase decision. There is simultaneous significant influence of motivation, belief and attitudes, occupation, economic situation, personality and self-concept, and lifestyle toward consumer purchase decision with adjusted R square is 47.8%. The most significance value from all independent variables toward dependent variable is lifestyle.